2019
DOI: 10.1016/j.psychres.2019.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and correlates of low vitamin D in schizophrenia, other psychoses and non-psychotic depression – The Northern Finland Birth Cohort 1966 study

Abstract: Title Vitamin D status and correlates of low vitamin D in schizophrenia, other psychoses and non-psychotic depression-The Northern Finland Birth Cohort 1966 study Article type Full Length Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
12
1
Order By: Relevance
“…Contrary to our results, a study has concluded that serum vitamin D levels were lower in patients with schizophrenia compared to patients with MDD and to healthy controls [57]. In another study, no differences were found in vitamin D level between schizophrenia and non-psychotic depression [47]. This finding warrants further investigation and needs to be replicated on a wider scale to be confirmed.…”
Section: Vitamin D Status In the Depression Group Vs Schizophrenia Gcontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to our results, a study has concluded that serum vitamin D levels were lower in patients with schizophrenia compared to patients with MDD and to healthy controls [57]. In another study, no differences were found in vitamin D level between schizophrenia and non-psychotic depression [47]. This finding warrants further investigation and needs to be replicated on a wider scale to be confirmed.…”
Section: Vitamin D Status In the Depression Group Vs Schizophrenia Gcontrasting
confidence: 99%
“…Other studies had equivocal results [44,46]. For example, one study found no difference in serum vitamin D level between depression and healthy controls [47], which could be attributed to different study design; while we used standardized tool for psychiatric diagnoses, they used register-based diagnoses.…”
Section: Vitamin D Status In the Patient Groups And Healthy Controlsmentioning
confidence: 88%
See 2 more Smart Citations
“…Three observational studies have been published since the most recent meta-analysis. [96][97][98] In these studies, the relationship between depression and VIT-D deficiency was less clear. One study failed to find a significant difference in participants with non-psychotic depression and controls.…”
Section: Proof Of Principle Laboratory Findingsmentioning
confidence: 99%